The Psychopolitics of Affect in Halle Butler’s Novels - Bartłomiej Musajew (European Journal of American Studies)
Drawing on the concept of psychopolitics by Byung-Chul Han, this article discusses how the replacement of biopolitical technologies of power by the soft psychopolitical technologies of power is displayed in Halle Butler’s novels. The article starts with the discussion of three psychopolitical models: 1) algorithmic governmentality, 2) therapy culture, 3) emotional capitalism. Then, it shows how these models are played out in Butler’s novels through the presence of characters with undisciplined bodies, and through the disjunction between self-perception and perception by others.